Determination of xylazine in drug-spiked drinks using gas chromatography for forensic investigation - Sadiq, Nabeesathul Sumayya Mohamed (2022)
Xylazine, a veterinary drug known for its sedative, anaesthesia, and analgesia effects, had recently reported its utilisation in drug facilitated crimes (DFC). Victims are incapacitated after consumption of drug-spiked drinks and subsequently exposed to the risk of robbery and sexual assault. This study aimed to establish a laboratory-based gas chromatography method to detect and quantify xylazine in drug-spiked drink samples appearing in liquid, droplet, and dry forms. In many instances, the suspected drug-spiked drink samples are available at the scene but the concentration level of xylazine could be very low or restricted by its recoverable amount for forensic testing. In this study, a gas chromatography-mass spectroscopy method was developed to detect the presence of xylazine, and a gas chromatography-flame ionisation detector method was validated for quantification of the substance. Subsequently, xylazine from four different drink samples present in three different physical forms, simulating the possible forensic settings; were recovered and determined. A validated method for the determination and quantification of xylazine within 15 minutes was reported. The limit of detection and limit of quantification of the method were determined at 0.08 μg/mL and 0.26 μg/mL, respectively. A good linearity was achieved with correlation coefficient of 0.997. Intra-day and inter-day precisions for the method were ranged at 0.5 - 0.7% and 1.6 – 3.9%, respectively. Good accuracy was also reported, ranging between 97.3% and 100.7%. For the recoveries of xylazine from four different drinks tested in this study, the amount of xylazine contained in a liquid drink sample could be quantified with recoveries greater than 77%. This study evidenced that limited volume of leftover spiked drink samples, and even the dried samples; did not hinder the recovery of the targeted drug. Trace xylazine that appeared in residual droplets or dried form within a container can be detected at a recovery percentage at least 40%. To conclude, a gas chromatographic method was successfully established for the determination of residual xylazine in drug-spiked drinks that can then provide valuable investigative technique to laboratory analysts and crime scene officers in DFC investigations.